1990
DOI: 10.1161/01.cir.82.6.2075
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular regional wall stress in dilated cardiomyopathy.

Abstract: Left ventriculography with simultaneous pressure micromanometry was performed in 11 normal control subjects and 17 patients with dilated cardiomyopathy (DCM). Left ventricular silhouettes in the right anterior oblique projection were divided into eight areas, and regional wall stress was computed by Janz's method in each area excluding the two most basal areas. Wall stress was higher in DCM patients than in control subjects (p<0.01). The percent area changes from end diastole to end systole in each area were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 47 publications
3
32
1
2
Order By: Relevance
“…Hayashida et al showed that wall stress in patients with IDCM was maximal in the basal segments and minimal in the apical segments. 19 Based on the above findings, we suggest that LVA formation in patients with IDCM occurs when high peak systolic pressure in the left ventricle (as shown in our patients) imposes high levels of stress on a posterobasal wall which is weakened by fibrosis in a manner similar to the expansion of a soap bubble (figure 3). The LVA location in FDCM is mainly at the anterior or apical walls, and the mechanism of cardiac damage differs, which suggests that the pathogenesis of LVA formation in FDCM and IDCM may differ.…”
Section: Hypothesissupporting
confidence: 63%
See 1 more Smart Citation
“…Hayashida et al showed that wall stress in patients with IDCM was maximal in the basal segments and minimal in the apical segments. 19 Based on the above findings, we suggest that LVA formation in patients with IDCM occurs when high peak systolic pressure in the left ventricle (as shown in our patients) imposes high levels of stress on a posterobasal wall which is weakened by fibrosis in a manner similar to the expansion of a soap bubble (figure 3). The LVA location in FDCM is mainly at the anterior or apical walls, and the mechanism of cardiac damage differs, which suggests that the pathogenesis of LVA formation in FDCM and IDCM may differ.…”
Section: Hypothesissupporting
confidence: 63%
“…The regional asynergy may be related to the heterogeneity of local wall fibrosis and local wall stress. [17][18][19] Juillière et al demonstrated that regional myocardial perfusion abnormalities were predominant in the myocardial regions delineating the anteroposterior axis of the left ventricle. 17 Local fibrosis occurred more frequently on the anterior wall or posterior wall, while less frequently on the lateral or septal wall.…”
Section: Hypothesismentioning
confidence: 99%
“…During exercise, in ischemic heart disease the left ventricle might have a worse preserved adaptation to excessive wall stress than in idiopatic cardiomyopathy, due to the presence of akinetic and dyskinetic cardiac segments [17,18]. A role has been proposed for the presence and severity of mitral regurgitation, which have been shown to negatively influence peak VO2 [7].…”
Section: Discussionmentioning
confidence: 99%
“…14,15,17,18,27 We also limited our analysis to DCM patients with widened QRS complexes, and it remains possible that some individuals with more narrow complexes might also benefit. Previous studies have reported regional wall motion abnormalities, heterogeneous wall stress, and myocardial perfusion in DCM patients with normal-appearing epicardial vessels, 28,29 although none reported QRS durations to test correlations with these phenomena. Certainly, surface ECG-based estimates may underestimate the temporal spread of depolarization if early and late portions have relatively low voltages.…”
Section: Study Design Limitationsmentioning
confidence: 98%